2022
DOI: 10.1002/ueg2.12266
|View full text |Cite
|
Sign up to set email alerts
|

Barrett Esophagus: Quality of life and factors associated with illness perception

Abstract: Background Health‐related Quality of life (HRQoL) in patients with Barrett's esophagus (BE), a premalignant condition, may be influenced by gastroesophageal reflux disease (GERD) symptoms and the risk of developing esophageal adenocarcinoma. Methods We aim to investigate HRQoL in non‐dysplastic Barrett Esophagus (NDBE) patients, identify factors associated with a negative illness perception of the diagnosis BE and compare outcomes between patients treated in a specialized BE center with non‐expert centers. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…Other studies confirm this and have shown that anxiety and depression appear to be associated with greater cancer worry; likewise, a high symptom burden is seen in those with high cancer worry. 13 19 Despite their high CWS, a large proportion of the pretreatment and post-treatment groups underestimate their risk (79.7% pre and 57.9% post therapy); this may be reflective of patients finding the understanding of numerical estimates of risk difficult to interpret. 27 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Other studies confirm this and have shown that anxiety and depression appear to be associated with greater cancer worry; likewise, a high symptom burden is seen in those with high cancer worry. 13 19 Despite their high CWS, a large proportion of the pretreatment and post-treatment groups underestimate their risk (79.7% pre and 57.9% post therapy); this may be reflective of patients finding the understanding of numerical estimates of risk difficult to interpret. 27 …”
Section: Discussionmentioning
confidence: 99%
“…There was an unfortunate loss of recruited subjects between pre and post groups, this was in part due to the clinical picture changing but there was a considerable issue with COVID-19 causing delays to treatment and some patients were still awaiting their ET at completion of the study. A similar cohort study halted their recruitment during the initial phase of the pandemic 13 ; however, as ET procedures were protected in the UK, we continued recruitment during this time. Nonetheless, fewer patients were seen face to face in clinic, front-line working was required of the clinical research staff and research nurses were redeployed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…BE is known is a result of longstanding GERD. Previous studies found the majority of the non-dysplastic BE cohort reported good re ux symptom control 9,11 . A previous study showed re ux symptoms as an important factor for negative illness perception on BE 11. To the best of our knowledge there are no data on GI symptoms related to cancer worry or cancer recurrence in patients during the period after receiving ET for BE dysplasia or early esophageal cancer.…”
Section: Introductionmentioning
confidence: 93%